PERANAN LEMBAGA SOSIALTERHADAP PEMBINAAN MORAL REMAJA DI KENAGARAIAN BATU GADANGKABUPATEN PADANG PARIAMAN - Silvia Anggreni BP; Befrido Ilham; Andika Dirsa (Ensiklopedia of Journal, 2023)
This research was backgrounded by the discovery of the role of Social Institutions in the form of Family Institutions, Educational Institutions, Religious Institutions and Legal Institutions in fostering adolescent morale in Kanagarian Batu Gadang, Padang Pariaman Regency. The purpose of this study is to find out how moral coaching is carried out by Social Institutions and to find out what obstacles are experienced by Social Institutions in fostering adolescent morale in Kanagarian Batu Gadang.            This type of research is qualitative research with the research method is descriptive, which is taken using purposive sampling techniques. Data were collected by observation techniques, interviews and documentation. The data validity test is to use trigulation techniques. This research data analysis technique was carried out using techniques from Milles and Huberman, namely: (1) the data collection process, (2) data reduction, (3) data presentation and (4) withdrawal of accuracy or verification. The informants in this study were each social institution in Nagari Batu Gadang, namely Parents, Teachers, Alim Ulama and the Police.            Based on the results of data analysis and discussion, it is concluded that the role of Social Institutions in fostering adolescent morale is: conveying to adolescents through proselytizing and Islamic religious guidance and providing counseling on the effects of deviant behavior. The obstacles faced by Social Institutions in guiding the morals of adolescents are: (a) Family institutions: the influence of an unfavorable environment and the lack of communication established in the family, (b) Educational institutions: teachers are faced with students who are difficult to advise and do not want to listen to advice, (c) Agam institutions: adolescents find it difficult to listen to advice so that scholars choose to be silent in advising them, (d) Legal institutions: communities that do not contribute to reporting perpetrators of deviance. As well as efforts to overcome the obstacles faced by Social Institutions are: (a) Holding religious recitations or lectures, (b)Paying attention to the environment of youth association, and (c) Supervising and providing threats in the form of reporting if they commit deviant behavior.Keywords: Social Institutions, Moral Construction, and Teenagers.